Inactivation of Giardia intestinalis cysts in water using a sonochemical method based on mid-high-frequency waves (2023)
ABSTRACT: Giardia intestinalis is a pollutant of food and water, resistant to conventional disinfection treatments and its elimination requires effective methods action. Herein, mid-high-frequency ultrasound (375 kHz), which produces HO• and H2O2, was used as an alternative method of treatment to inactivate Giardia intestinalis cysts in water. The effect of ultrasound power (4.0, 11.2, 24.4 W) on the sonogeneration of radicals was tested, showing that 24.4 W was the condition most favorable to treat the parasite. The viability of the protozoan cysts was evaluated using the immunofluorescence technique and vital stains, showing this protocol was useful to quantify the parasite. The sonochemical method (at 375 kHz and 24.4 W) was applied at different treatment times (10, 20, and 40 min). A significant decrease in the protozoan concentration (reduction of 52.4% of viable cysts) was observed after 20 min of treatment. However, the extension of treatment time up to 40 min did not increase the inactivation. Disinfecting action was associated with attacks on the Giardia intestinalis cyst by sonogenerated HO• and H2O2 (which may induce structural damage, even the cell lysis). For future work is recommended to test combinations with UVC or Fenton process to enhance the inactivating action of this method. • Mid-high-frequency ultrasound produces HO• and H2O2 profitable to inactivate Giardia intestinalis. • Immunofluorescence technique and vital stains allowed us to quantify the parasite viability. • Giardia intestinalis cysts concentration decreased by 52.4% after only 20 min of sonication.